DESCRIPTION AND CRYSTAL STRUCTURE OF MANGANLOTHARMEYERITE, CA(MN3+,□,MG)2{ASO4,[ASO2 (OH 2], FROM THE STARLERA Mn DEPOSIT, SWISS ALPS, AND A REDEFINITION OF LOTHARMEYERITE - Brugger J.; Krivovichev S.V.; Kolitsch U.; Andrut M.; Meisser N.; Ansermet S.; Burns P.C. (My University, 2002)
Manganlotharmeyerite, Ca(Mn3+,square,Mg)(2){AsO4,[AsO2(OH)(2)]}(2)(OH,H2O)(2), is a new member of the tsumcorite group of minerals, of general formula Me(1)Me(2)(2)(XO4)(2)(OH,H2O)(2), in which Me(1) represents Pb2+, Ca2+, Na+ and Bi3+, Me(2) represents Fe3+, Mn3+, Cu2+, Zn2+, Co2+, Ni2+, Al3+ and Mg2+, and X can be P5+, As5+, V5+ or S6+. Manganlotharmeyerite occurs with sailaufite, (Ca,Na,square)(2)Mn3O2(AsO4)(2)(CO3).3H(2)O, tilasite and calcite in discordant veinlets within massive braunite ores at the Starlera Mn deposit in the Eastern Alps of Switzerland. Manganlotharmeyerite and the associated arsenates are the product of the latest stage of As remobilization during retrograde Alpine metamorphism of Triassic carbonate-hosted, syngenetic exhalative Mn-ores. Manganlotharmeyerite forms elongate platy crystals and aggregates up to I mm in length, but optically homogeneous crystals do not exceed 100 mum in length. The mineral has a Mobs hardness of about 3, with a D-calc of 3.75(2) and a D-meas of 3.77(2) g/cm(3); it is brittle, with an irregular fracture and a distinct cleavage parallel to {001}. Manganlotharmeyerite is transparent to translucent with an adamantine luster. It is brown-red to dark reddish orange in color, and has a light brown streak. The new mineral species is biaxial positive, with alpha 1.785(5), beta 1.814(5) and gamma 1.854(5), 2V(meas.) about 85degrees, 2V(calc.) 82degrees, dispersion r < v weak. The average composition of the mineral, measured with an electron microprobe, is [Wt%]: V2O5 0.67, As2O5 53.41, MgO 3.95, Mn2O3 16.70, CaO 12.42, Fe2O3, 0.91, NiO 1.07, minor quantities (<1 wt%) of Al2O3, SrO, Na2O, CoO, and ZnO, H2Ocalc 8.84, sum 99.3, resulting in the empirical chemical formula (Ca0.94Sr0.01Na0.01)(Mn3+ (0.45)square(0.26)Mg(0.20)Ni(0.03) Fe0.02Zn0.02Al0.01Co0.01)(2)(As0.98V0.02)(2)O10H4.16. The structural chemical formula of the mineral derived on the basis of the crystal-structure refinement is Ca(Mn3+ (0.59)square(0.24)Mg(2+) (0. 17))(2){AsO4)(0.76)[AsO2(OH)(2)](0.24)}(2)[(OH)(0.59)(H2O)(0.41)](2). Manganlotharmeyerite is monoclinic, C2/m, a 9.043(1), b 6.2314(7), c 7.3889(9) Angstrom, beta 116.392(2)degrees, V 372.99(9) Angstrom(3) and Z = 2. Single-crystal structure refinement (R-1 = 0.025) confirmed isotypy with the tsumcorite structure. The strongest ten lines in the X-ray powder-diffraction pattern [d in Angstrom (I)(hkl)] are: 4.93(80)((1) over bar 10), 4.61(50)(111), 3.426(60)((2) over bar 02), 3.182(100)((1) over bar 12), 3.122(50)(020), 2.927(70)(201), 2.822(70)(0(2) over bar 1), 2.718(80)((3) over bar 11), 2.555(100)((2) over bar 21(3) over bar 12), 2.134(70)(202,221). Unit-cell parameters from the powder-diffraction data are: a 9.074(5), b 6.239(3), c 7.406(4), beta 116.60(3)degrees. The nomenclature of members of the tsumcorite group with Me(l) = Ca and X = As (lotharmeyerite subgroup) is based on the occupant of the Me(2) site. Manganlotharmeyerite represents the Mn3+-dominant member of the group, and lotharmeyerite is redefined to represent the Zn-dominant member. The lotharmeyerite subgroup now contains six phases: cabalzarite with Me(2) = Mg, ferrilotharmeyerite (Fe3+), cobaltlotharmeyerite (Co), nickellotharmeyerite (Ni), lotharmeyerite (Zn) and manganlotharmeyerite (Mn3+).